Effects of decomposition on carbon and nitrogen stable isotope values of muscle tissue of varying lipid content from three aquatic vertebrate species. (18th January 2017) - Yurkowski, David J.; Hussey, Anna J.; Hussey, Nigel E.; Fisk, Aaron T.
Abstract : Rationale: Stable isotopes are a prominent tool in animal ecology where data is obtained from analyzing animal tissues, which are typically stored prior to analysis. However, the effect of decomposition on the reliability of stable isotope ratios from animal tissue prior to storage has been seldom studied. Here, we examine the long‐term effects of freezing and decomposition of animal tissue on δ 13 C and δ 15 N values across three different aquatic species of varying lipid content. Methods: Ringed seal, lake trout and Greenland shark muscle were divided into different treatment groups and analyzed for their δ 13 C values, carbon content (%C), δ 15 N values, and nitrogen content (%N) at specific time intervals. The intervals included days 0, 128 and 700 for the frozen storage treatment and at days 0, 1, 2, 4, 8, 16, 32, 64, 128 and 256 for the tissue decomposition treatment in open and closed vials at room temperature. Results: The difference in δ 13 C and δ 15 N values between the control and days 128 and 700 for the frozen treatment was minimal and not significant for any species. Generally, significant decreases in carbon (%C) and nitrogen (%N) content and significant increases (>0.5‰) in δ 13 C and δ 15 N values occurred for muscle of each species left to decompose for 256 days, probably due to the preferential uptake of lighter isotopes during decomposition by microbes. However, the magnitude of change in the δ 13 C and δ 15 N values up to 8 days in both treatments was low (generally ≤0.1‰) and not significant across most species. Conclusions: Freezing for extended time periods (up to 700 days) is a viable storage technique for stable isotope analysis of aquatic animal muscle tissue across a range of lipid contents. Muscle tissue left to decompose at room temperature showed no significant change in δ 13 C and δ 15 N values after 8 days, and such tissues would still be reliable for ecological interpretations. However, caution should be used for decomposed tissue for >8 days as the δ 13 C and δ 15 N values will probably be artificially high. Copyright © 2016 John Wiley & Sons, Ltd.